Social Marketing Challenges in Western Balkans: Evidence From Kosovo - Rrustemi, Visar; Mladenović, Dušan; Jusufi, Gezim (Medicine, Law & Society, 2021)
In a global world, doing business in heavy industry is becoming a concern to the environment. The need for production, export, and consumption under these circumstances has come as a challenge for marketers, consumers and surrounding residential population. The Western Balkan countries include Albania, Bosnia and Herzegovina, North Macedonia, Serbia, Montenegro and Kosovo. Kosovo has witnessed a considerable economic transformation during recent years, but is has fallen short of considering and implementing a strategy for the preservation of the environment. Kosovo is relatively rich with underground and surface resources, having large quantities of minerals and coal. But despite this, Kosovo continues to be the most underdeveloped country in the region. Exploiting these resources can have a great impact on economic growth and with it, consumer needs are more satisfied. Social marketing has a major impact on the activities of businesses in these areas and ensures that these businesses operate in accordance with certain rules and laws. This would also help in matters of general health of the population. Through Pearson's correlation and case studies, recommendations and conclusions will be given on the studied topic. The results show that there are positive and negative relationships between the variables which are significant.